Investigation of nerve pathways mediating colorectal dysfunction in Parkinson's disease model produced by lesion of nigrostriatal dopaminergic neurons. Issue 9 (8th June 2020) - Chai, Xin‐yi; Diwakarla, Shanti; Pustovit, Ruslan V.; McQuade, Rachel M.; Di Natale, Madeleine; Ermine, Charlotte M.; Parish, Clare L.; Finkelstein, David I.; Furness, John B.
Abstract: Background: Gastrointestinal (GI) dysfunction, including constipation, is a common non‐motor symptom of Parkinson's disease (PD). The toxin 6‐hydroxydopamine (6OHDA) produces the symptoms of PD, surprisingly including constipation, after it is injected into the medial forebrain bundle (MFB). However, the mechanisms involved in PD‐associated constipation caused by central application of 6OHDA remain unknown. We investigated effects of 6OHDA lesioning of the MFB on motor performance and GI function. Methods: Male Sprague Dawley rats were unilaterally injected with 6OHDA in the MFB. Colorectal propulsion was assessed by bead expulsion after 4 weeks and by recording colorectal contractions and propulsion after 5 weeks. Enteric nervous system (ENS) neuropathy was examined by immunohistochemistry. Key Results: When compared to shams, 6OHDA‐lesioned rats had significantly increased times of bead expulsion from the colorectum, indicative of colon dysmotility. Administration of the colokinetic, capromorelin, that stimulates defecation centers in the spinal cord, increased the number of contractions and colorectal propulsion in both groups compared to baseline; however, the effectiveness of capromorelin in 6OHDA‐lesioned rats was significantly reduced in comparison with shams, indicating that 6OHDA animals have reduced responsiveness of the spinal defecation centers. Enteric neuropathy was observed in the distal colon, revealing that lesion of the MFB has downstream effects at the cellular level, remote from the site of 6OHDA administration. Conclusions & Inferences: We conclude that there are trans‐synaptic effects of the proximal, forebrain, lesion of pathways from the brain that send signals down the spinal cord, at the levels of the defecation centers and the ENS. Abstract : Lesion of the medial forebrain bundle caused reductions in the responses to activation of the defecation centers in the lumbo‐sacral spinal cord, reduced ENS‐mediated propulsion, and enteric neuropathy 4‐5 weeks later, indicating trans‐synaptic changes in neuronal properties.